Analysis of Financial Statement Performance Ratios in Cigarette Subsector Companies Listed on The IDX - Faizah, Salma; Ramadan, Yanuar; Kurniawan, Hengki; El Barqa, Malviyola; Baharsyah, Ilham Baihaqi (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2025)
Assessment of the company's financial performance is critical to determine the company's financial condition so that the company's success rate can be known during a specific period and as an evaluation material for management. The data used in this study are the financial statements of cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX) for 2019-2023. The data analysis technique in this study is to analyze financial ratios, which include liquidity ratio, activity ratio, solvency ratio, and profitability ratio. The results showed that for the liquidity ratio of PT Wismilak Inti Makmur Tbk. Showed financial performance in good condition, on the activity ratio of PT Gudang Garam Tbk. and PT Hanjaya Mandala Sampoerna Tbk. Showed financial performance in good condition, based on PT Wismilak Inti Makmur Tbk's solvency ratio and PT Gudang Garam Tbk. Showed financial performance in good condition, and on the profitability ratio of the financial performance of the companies PT Indonesian Tobacco Tbk. and PT Hanjaya Mandala Sampoerna Tbk. in good condition.